Efektivitas Pembelajaran E-Learning Pelatihan Dasar Calon Pegawai Negeri Sipil di Badan Siber dan Sandi Negara - Nur Rohmah, Ratri (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2021)
Technology and covid-19 pandemic has become the main trigger for implementation of distance learning in Basic Training Civil Servants at BSSN. E-learning has many differences compared to the conventional methods that were applied previously. We hoped e-learning activities running well so they can achieve the learning objectives. This study seeks to reveal an overview of the effectiveness of e-learning Basic Training Civil Servants. The method used in this research is descriptive research. Data collection was carried out by observation, interview and literature study methods. Interviews were conducted with managers, administrators, teachers and training participants. Based on the research, the results is e-learning Basic Training Civil Servants run effectively. This can be seen from the data that shows that learning has succeeded in achieving the set instructional goals, is able to provide an attractive learning experience, is able to actively involve participants, and the facilities that support the teaching and learning process are fulfilled properly. In addition, it was also found that synchronous model was more attractive to participants than asynchronous. Participants feel that synchronous model can help them focus more and increase motivation when learning. To improve the implementation of online learning in the future, it is suggested to increase synchronous method and delivery material through gamification application to make leraning more interesting